Trends in antimicrobial resistance among Escherichia coli from defined infections in humans and animals. (12th February 2020) - Bourély, Clémence; Coeffic, Thomas; Caillon, Jocelyne; Thibaut, Sonia; Cazeau, Géraldine; Jouy, Eric; Jarrige, Nathalie; Chauvin, Claire; Madec, Jean-Yves; Haenni, Marisa; Leblond, Agnès; Gay, Emilie
Abstract: Objectives: To characterize and compare resistance trends in clinical Escherichia coli isolates from humans, food-producing animals (poultry, cattle and swine) and pets (dogs and cats). Methods: Antibiogram results collected between January 2014 and December 2017 by MedQual [the French surveillance network for antimicrobial resistance (AMR) in bacteria isolated from the community] and RESAPATH (the French surveillance network for AMR in bacteria from diseased animals) were analysed, focusing on resistance to antibiotics of common interest to human and veterinary medicine. Resistance dynamics were investigated using generalized additive models. Results: In total, 743 637 antibiograms from humans, 48 170 from food-producing animals and 7750 from pets were analysed. For each antibiotic investigated, the resistance proportions of isolates collected from humans were of the same order of magnitude as those from food-producing animals or pets. However, resistance trends in humans differed from those observed in pets and food-producing animals over the period studied. For example, resistance to third-generation cephalosporins and fluoroquinolones was almost always below 10% for both humans and animals. However, in contrast to the notable decreases in resistance observed in both food-producing animals and pets, resistance in humans decreased only slightly. Conclusions: Despite several potential biases in the data, the resistance trends remain meaningful. The strength of the parallel is based on similar data collection in humans and animals and on a similar statistical methodology. Resistance dynamics seemed specific to each species, reflecting different antibiotic-use practices. These results advocate applying the efforts already being made to reduce antibiotic use to all sectors and all species, both in human and veterinary medicine.